Suppression of interferon α and γ response by Huwe1-mediated Miz1 degradation promotes SARS-CoV-2 replication - Arunagiri, Vinothini; Cooper, Laura; Dong, Huali; Class, Jake; Biswas, Indrani; Vahora, Sujan; Deshpande, Riddhi; Gopani, Khushi H.; Hu, Guochang; Richner, Justin M.; Rong, Lijun; Liu, Jing (Frontiers in Immunology, 2024)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been demonstrated to limit the host interferon response; however, the underlying mechanism remains unclear.Here, we found that SARS-CoV-2 infection upregulated the E3 ubiquitin ligase Huwe1, which in turn facilitated the degradation of the transcription factor Miz1. The degradation of Miz1 hampered interferon alpha and gamma responses, consequently fostering viral replication and impeding viral clearance. Conversely, silencing or inhibiting Huwe1 enhanced the interferon responses, effectively curbing viral replication. Consistently, overexpressing Miz1 augmented the interferon responses and limited viral replication, whereas silencing Miz1 had the opposite effect. Targeting Huwe1 or overexpressing Miz1 elicited transcriptomic alterations characterized by enriched functions associated with bolstered antiviral response and diminished virus replication. Further study revealed Miz1 exerted epigenetic control over the transcription of specific interferon signaling molecules, which acted as common upstream regulators responsible for the observed transcriptomic changes following Huwe1 or Miz1 targeting. These findings underscore the critical role of the Huwe1-Miz1 axis in governing the host antiviral response, with its dysregulation contributing to the impaired interferon response observed during COVID-19.